2020
DOI: 10.1371/journal.pone.0238923
|View full text |Cite
|
Sign up to set email alerts
|

Maternal supplementation with Bifidobacterium breve M-16V prevents their offspring from allergic airway inflammation accelerated by the prenatal exposure to an air pollutant aerosol

Abstract: Bifidobacterium breve M-16V is a probiotic bacterial strain with efficacy in infants achieved by suppressing T-helper type (Th) 2 immune responses and modulating the systemic Th1/ Th2 balance. Exposure to air pollution during pregnancy increases asthma susceptibility in offspring. The aim of this study was to investigate the effects of the maternal intake of B. breve M-16V on susceptibility to asthma accelerated by prenatal exposure to air pollution. The intake of B. breve M-16V in residual oil fly ash (ROFA)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 54 publications
0
14
0
1
Order By: Relevance
“…An interesting aspect is that most probiotics are given orally; however, a new approach was tested by giving probiotics ( Lactobacillus paracasei NCC2461 [ 26 ] and Lactobacillus rhamnosus GG [ 27 ] in mice through the nose and showed benefits in reducing inflammation of the lungs [ 28 ]. The probiotic Bifidobacterium breve M-16V administered to pregnant mice was shown to be effective in lowering eosinophils in the broncho-alveolar lavage fluid of neonatal mice and reduced allergic lung inflammation in mice exposed to air pollution [ 29 ]. In another animal study, the intranasal administration of Lactobacillus rhamnosus GG (LGG), but not Lactobacillus rhamnosus GR-1, suppressed airway hyper-reactivity and reduced the counts of eosinophils, IL-13 and IL-5 in broncho-alveolar fluid [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An interesting aspect is that most probiotics are given orally; however, a new approach was tested by giving probiotics ( Lactobacillus paracasei NCC2461 [ 26 ] and Lactobacillus rhamnosus GG [ 27 ] in mice through the nose and showed benefits in reducing inflammation of the lungs [ 28 ]. The probiotic Bifidobacterium breve M-16V administered to pregnant mice was shown to be effective in lowering eosinophils in the broncho-alveolar lavage fluid of neonatal mice and reduced allergic lung inflammation in mice exposed to air pollution [ 29 ]. In another animal study, the intranasal administration of Lactobacillus rhamnosus GG (LGG), but not Lactobacillus rhamnosus GR-1, suppressed airway hyper-reactivity and reduced the counts of eosinophils, IL-13 and IL-5 in broncho-alveolar fluid [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Exposure of the pregnant mother to air pollution increases asthma susceptibility of the newborn and later on. Therefore, Bifidobacterium breve M-16V might contribute to reducing asthma in a population living in highly polluted areas [ 29 ]. In 2014, the Panda Study showed that giving a probiotic mixture postnatally (two Bifidobactera spp.…”
Section: Resultsmentioning
confidence: 99%
“…Total 29 faecal samples (untreated mice fed control or tannin diet, n = 5 each; DSS-treated mice fed control or tannin diet, n = 9 or 10, respectively) were used in the following procedure. Extraction of bacterial DNA, sequencing, and software analysis have been described previously 48 . Briefly, faecal samples (20 mg) from the mice were crashed in saturated phenol by glass beads (300 mg, 0.1 mm in diameter) and a Multi-Beads Shocker (Yasui Kikai Co., Osaka, Japan), and then bacterial DNA was extracted by phenol/chloroform and isopropanol precipitation.…”
Section: Methodsmentioning
confidence: 99%
“…Studies conducted in an animal model of ovalbumin (OVA) sensitization in the neonatal stage with a previous treatment period with Bifidobacterium strains have demonstrated their potential to alleviate the risk of IgE-mediated allergies in adulthood, by exhibiting a minor increase in serum IgE levels induced by intraperitoneal-OVA challenge in the adult period and significantly higher IL-10 levels than in the control group [167]. Additionally, a positive effect of bifidobacteria treatment in models of airway inflammation was demonstrated by a reduction of allergic lung inflammation [168,169]. Regarding food allergy, it was suggested to occur due to defective oral tolerance in the neonatal stage [171], and various preclinical studies of a diet supplemented with prebiotic oligosaccharides and B. breve M-16V tested its capacity to satisfactorily prevent allergy development in an early life murine model of orally induced cow-milk allergy [171,172].…”
Section: Animal Modelsmentioning
confidence: 99%